ANALISIS SEGMEN PASAR DAN PERILAKU NASABAH BANK SYARIAH: KAJIAN HUKUM ISLAM TERHADAP PRODUK HSBC AMANAH INDONESIA - Mursid, Mansur Chadi; Irviana, Rr. Kathrin (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2012)
The purpose of this research is for identifying market segment and customer behavior toward Islamic banking and its marketing implications in all regions of DKI Jakarta. The analytical tools applied are analysis of cluster, factor and descriptive. The result of this research for segmentation aspect showed the characteristics and size of each market segment of Islamic banks. The market segment consists of syariah loyalist, floating mass and conventional loyalist. From this research, floating mass segment is the most potential segment due to its market size compared to syariah loyalist and conventional loyalist segments.DOI: 10.15408/aiq.v4i2.2532